Prevalencia de trastornos mentales en usuarios de consulta psicológica en una universidad colombiana (2011)
ABSTRACT: This is a prevalence study of the mental disorders on psychological counseling users. A sample of 103 outpatients who were administered the M.I.N.I test was used. The outcome showed that 70.6% of the patients had manifested mental disorders once or more in their lifetime, with mood disorders having more prevalence, followed by anxiety disorders, and non-alcoholic substance use. The disorders with greater prevalence in woman were depressive disorders, anxiety disorders, social phobia, and hypomania. For men it was found that disorders related to non-alcoholic substance abuse, depression, anxiety, mania, alcohol abuse, and dependence were more prevalent.